2019
DOI: 10.1002/micr.30425
|View full text |Cite
|
Sign up to set email alerts
|

Functional penile replantation after traumatic avulsion amputation below the pubis: A case report

Abstract: Penile amputation is a rare injury with significant posttraumatic ramifications. We present a case of successful immediate replantation after traumatic penile avulsion in a 52‐year‐old male patient. The patient reported his penis was caught in machinery during a boating accident, and avulsed at the level of the pubis. Immediate replantation of this proximal avulsion injury with no suitable proximal arterial stumps required transfer of the superficial inferior epigastric artery for arterial inflow. One artery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Fortunately, the patient recovered his penile function, albeit, very gradually over three years. [18] Regarding other imaging modalities, predominantly Magnetic Resonance Imaging (MRI), previous work has only been focused on vascular abnormalities like priapism, Mondor disease, traumatic injuries including penile fracture and contusion, congenital anomalies in addition to penile malignancies. [31][32][33] Hence, current literature fails to provide adequate knowledge on the value of MRI in following clinical cases of penile amputation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, the patient recovered his penile function, albeit, very gradually over three years. [18] Regarding other imaging modalities, predominantly Magnetic Resonance Imaging (MRI), previous work has only been focused on vascular abnormalities like priapism, Mondor disease, traumatic injuries including penile fracture and contusion, congenital anomalies in addition to penile malignancies. [31][32][33] Hence, current literature fails to provide adequate knowledge on the value of MRI in following clinical cases of penile amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies reporting first-week post-operative Doppler evaluation, two investigations reported no vascularity in Doppler ultrasound [19,26], three studies did not provide any information of the post-operative Doppler findings [16,22,25] and one study reported that Doppler signal was positional, with complete loss of signal with adduction of the legs. [18] The rest of the studies reported adequate blood flow.…”
Section: Studies Included In Quantitative Synthesismentioning
confidence: 94%
See 1 more Smart Citation
“…Some of the more common mechanisms include self-mutilation, domestic violence, trauma, and failed circumcision [2,4,6,7]. Less common injuries include boating accidents, animal bites, agricultural machinery accidents among others [8][9][10]. A series of penile amputations in ailand were maliciously performed in the 1970's by wives of unfaithful husbands [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since the location, degree, and manner of injury can vary greatly, penile amputations constitute a complicated clinical entity. Surgical treatment is technically difficult, and the resultant physical and psychological consequences are important 4 . Now we present here a case report of penile amputation during neonatal circumcision with an unexperianced practitioner.…”
Section: Introductionmentioning
confidence: 99%